Sex as a Biological Variable in Atherosclerosis - Man, Joshua J. (Circ Res, 2020)
Atherosclerosis is a chronic inflammatory vascular disease and the predominant cause of heart attack and ischemic stroke. Despite the well-known sexual dimorphism in the incidence and complications of atherosclerosis, there are relatively limited data in the clinical and pre-clinical literature to rigorously address mechanisms underlying sex as a biological variable in atherosclerosis. In multiple histological and imaging studies, overall plaque burden and markers of inflammation appear to be greater in men than women and are predictive of cardiovascular events. However, while younger women are relatively protected from cardiovascular disease, by the seventh decade the incidence of myocardial infarction in women ultimately surpasses that of men, suggesting an interaction between sex and age. Most pre-clinical studies in animal atherosclerosis models do not examine both sexes, and even in those that do, well-powered direct statistical comparisons for sex as an independent variable remain rare. This manuscript reviews the available data. Overall, male animals appear to have more inflamed yet smaller plaques compared to female animals. Plaque inflammation is often used as a surrogate endpoint for plaque vulnerability in animals. The available data supports the notion that rather than plaque size, plaque inflammation may be more relevant in assessing sex-specific mechanisms since the findings correlate with the sex difference in ischemic events and mortality and thus may be more reflective of the human condition. Overall, the number of pre-clinical studies directly comparing plaque inflammation between the sexes is extremely limited relative to the vast literature exploring atherosclerosis mechanisms. Failure to include both sexes and to address age in mechanistic atherosclerosis studies are missed opportunities to uncover underlying sex-specific mechanisms. Understanding the mechanisms driving sex as a biological variable in atherosclerotic disease is critical to future precision medicine strategies to mitigate what is still the leading cause of death of men and women worldwide.